Modelo SIG para selecção de locais para aterros de resíduos - Costa, Carlos Nunes (2003)
GIS MODEL FOR WASTE DISPOSAL SITES. Landfill is still the major method for waste disposal in the EU. The need to guarantee environmental protection and to follow a scientific and more transparent procedure of landfill site selection was the motivation to develop the GIS model presented in this paper. This work was developed under the auspices of an Interreg-funded EU project, by a team of Irish and Portuguese partners from University College Cork and the New University of Lisbon, and from local authorities in both countries, Cork County Council and Sesimbra Town Council.The theoretical GIS model consists of two steps. In the first step, data in vector structure and geo-processing techniques such as overlay and buffering are used to exclude areas unsuitable for landfill due to risk to the environment or human health. The exclusion factors considered in this step were grouped into “non-geological factors” and “geological and correlated factors”.The remaining residual areas, considered suitable for the location of landfills, may have some land parcels more suitable than others, and are thus further examined in the second step of the GIS model. This step is an automated raster-based process in which a series of parameters are used to classify each area in terms of high, moderate or low suitability for landfill. These parameters were also grouped into four different types: a) susceptibility to natural hazards; b) aquifer protection levels; c) land use; d) geo-environmental engineering. These parameters can also be weighted in order to provide different evaluation scenarios of the residual areas; extensions have been developed for ArcView GIS that will automatically calculate the weights for each category following inputs from the user. Study sites in both countries were used to test and validate the model. This paper presents the results obtained from the application of the model to Sesimbra Council in Portugal. The development of the landfill GIS model fulfils legislative and environmental obligations associated with site selection in a non-biased way, and the methodology aims at providing a clear and scientific rationale behind the choice of a site. Application of the model does not intend to substitute political decision but will provide decision makers (local authorities, waste management entities, etc.) with an important tool and a methodology that will aid their decision and enable them to conduct their own GIS landfill site selection screening process.